Missing links – national memorial sites in literature and education (Training and Practice : Journal of Educational Sciences, 2020)
Students in secondary and tertiary education of today meet few transcultural contemporary texts connected to the decisive moment of 1989, i.e. to the Pan-European Picnic on 19th August. Although, due to Pierre Nora, national memorial sites have become the part of scientific awareness and related national research has also been carried out, in my opinion these were only the outline. The research team of the Faculty of Arts at the University of Debrecen, named Hungarian Memorial Sites Research Team and established in 2010, aimed to set the French lieux de mémoire (memorial site) into Hungarian context. A database was also added and, according to my research, it has not changed since its formation. I guess the register of the national memorial sites may increase, and it could appear with a stronger focus in education as well. A part of the process could be the Pan-European Picnic as a memorial site, which entered the international literature of memory with the East Germans’ crossing the border.